Early-life dietary spray-dried plasma influences immunological and intestinal injury responses to later-life Salmonellatyphimurium challenge. Issue 5 (11th February 2015) - Boyer, P. E.; D'Costa, S.; Edwards, L. L.; Milloway, M.; Susick, E.; Borst, L. B.; Thakur, S.; Campbell, J. M.; Crenshaw, J. D.; Polo, J.; Moeser, A. J.
Abstract : Increasing evidence supports the concept that early-life environmental influences, including nutrition and stress, have an impact on long-term health outcomes and disease susceptibility. The objective of the present study was to determine whether dietary spray-dried plasma (SDP), fed during the first 2 weeks post-weaning (PW), influences subsequent immunological and intestinal injury responses to Salmonella typhimurium challenge. A total of thirty-two piglets (age 16–17 d) were weaned onto nursery diets containing 0, 2·5 % SDP (fed for 7 d PW) or 5 % SDP (fed for 14 d PW), and were then fed control diets (without SDP), for the remainder of the experiment. At 34 d PW (age 50 d), pigs were challenged with 3 × 10 9 colony-forming units of S. typhimurium . A control group (non-challenged) that was fed 0 % SDP in the nursery was included. At 2 d post-challenge, the distal ileum was harvested for the measurement of inflammatory, histological and intestinal physiological parameters. S . typhimurium challenge induced elevated ileal histological scores, myeloperoxidase (MPO), IL-8 and TNF, and increased intestinal permeability (indicated by reduced transepithelial voltage (potential difference) and elevated 4 kDa fluorescein isothiocyanate dextran (FD4) flux rates). Compared with S. typhimurium -challenged controls (0 % SDP), pigs fed the 5 % SDP-14 d diet exhibited reduced ileal histological scores, MPO levels, IL-8 levels and FD4 flux rates. Pigs fed the 5 % SDP-14 d nursery diet exhibited increased levels of plasma and ileal TNF-α in response to the challenge, compared with the other treatments. These results indicate that inclusion of SDP in PW diets can have an influence on subsequent immunological and intestinal injury responses induced by later-life S. typhimurium challenge.